Complications of lipoabdominoplasty without Scarpa fascia preservation versus classic abdominoplasty: a prospective blind study - João Maximiliano; Antonio Carlos Oliveira; Ciro Paz Portinho; Mauricio Farenzena; Matheus Reis; Tulio Serrano; Diego Dullius; Marcus Vinicius Martins Collares (Revista Brasileira de Cirurgia Plástica)
Introduction: Abdominoplasty is among the most commonly performed surgical procedures. Seroma is the most common local complication associated with abdominoplasty, with an average incidence of 10%. The highest incidence of postoperative (PO) seroma occurs on the eleventh postoperative day (POD). Abdominal ultrasound is the method of choice for diagnosing seroma after abdominoplasty. New techniques have emerged aiming to improve aesthetic results with fewer complications, such as lipoabdominoplasty described by Saldanha. However, recent anatomical studies have questioned the need for Scarpa fascia preservation recommended in the lipoabdominoplasty technique, describing that around 90% of the abdominal lymphatic system is in the subdermal plane, while the other 10% is in a deep lymphatic system near the abdominal aponeurosis. The objective is to compare the incidence of seroma in lipoabdominoplasty without Scarpa fascia preservation to that in classic abdominoplasty. Methods: Prospective blinded cohort in which 40 consecutive patients who underwent abdominoplasty without associated liposuction (n = 20) or lipoabdominoplasty (n = 20) at the Hospital de Clínicas of Porto Alegre between April 2016 and May 2017 were analyzed. All patients underwent abdominal wall ultrasonography on the tenth POD. Results: The incidence of seroma was 5% (n = 1) in the classic abdominoplasty group and 10% (n = 2) in the lipoabdominoplasty group, with no statistical difference. Conclusion: These results showed no statistically significant intergroup difference in seroma development.